Hemodialysis Minimal is the Future (Pakistan Journal of Kidney Diseases, 2021)
Father of Hemodialysis, Willelm Kolff a Dutch physician, during the terrible times of Nazi occupation risked his life to experiment and invent the first hemodialysis machine. One can imagine, that the power to do something good for your fellow human beings does not wait for the perfect times and facilities.
Keywords: hemodialysis; minimal; smaller machines